Nonlinear delay differential equations and their application to modeling biological network motifs - David S. Glass (Nature Portfolio, 2021)
Network motif models focus on small sub-networks in biological systems to quantitatively describe overall behavior but they often overlook time delays. Here, the authors systematically examine the most common network motifs via delay differential equations (DDE), often leading to more concise descriptions.